PENGARUH MEDIA PEMBELAJARAN DENGAN VAF TERHADAP PENGETAHUAN ANAK USIA SEKOLAH TENTANG RJP DI SDN KAMPUNGDALEM 3 DAN 4 KOTA KEDIRI - Wulansari, Yunita Wahyu; Wadjib, Yuyun Yueniwati Prabowowati; Suharsono, Tony (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
The number of bystander CPR as the first helper of out ofhospital cardiac arrest (OHCA) is stilllow in various countries. The effort that can be done is by providing CPR training in thecommunity. This study aims to analyze the influence of learning media with fabel animation video(VAF) to knowledge about CPR. This true experimental study with randomized subject, pretestposttest control group design have been done on 120 respondents divided into 2 groups that isVAF and module with three times measurement in SDN Kampungdalem 3 and 4 Kota Kediri. Theresult of this study indicate that in both groups has a significant influence on knowledge (p =0,000). Significant differences between VAF and module are on after and one week after CPRtraining. This suggest that CPR training using VAF provides more effective than module on CPRknowledge in children.